The Social Conflict During The French Revolution Era In "A Tale of Two Cities" by Charles Dickens: Social Conflict During The French Revolution Era In "A Tale of Two Cities" by Charles Dickens - Siahaan, Hery William; Satria, Robby (SCIENTIA JOURNAL, 2024)
This research aims to analyze the background and the cause of class conflict between the bourgeoisie and the proletariat related with the form of social class and what its impact towards the conflict between both classes. This study analyzes "A Tale of Two Cities" by Charles Dickens, a novel set against the backdrop of the French Revolution, with the focus on the depiction of social conflict. Published in 1859, Dickens used characters such as Dr. Manette, Lucie Manette, Sydney Carton, and Charles Darnay to depict the turmoil of the era. This research uses the theories of Max Weber and Karl Marx regarding power, authority and social structure, as well as the Marxist concept of capitalism regarding the domination of power by certain groups with a system of slavery and exploitation. This analysis examines the triggers for the French revolution in Paris, which reflected the social decline of French society, culminating in the stage of revolution and government terror. Social injustice and open conflict that occur in society are explained explanatory using a descriptive qualitative method approach. This analysis aims to reveal the problems of social conflict that occur within the bourgeoisie and proletariat society as well as analyzing social conflict.